Acid-base properties of non-protein nitrogen affect nutrients intake, rumen fermentation and antioxidant capacity of fattening Hu sheep - Zheng, Wenjin; Duan, Hongwei; Cao, Liwen; Mao, Shengyong; Shen, Junshi (Frontiers in Veterinary Science, 2024)
This study conducted a comparison of the effects of non-protein nitrogen with different acid-base properties on feed intake, rumen fermentation, nutrient digestion and antioxidant capacity in fattening Hu sheep. Sixteen fattening male sheep (31.43 ± 2.41 kg) with permanent rumen cannulas were randomly assigned to two dietary treatments: 1% urea and 1.78% ammonium chloride (NH4Cl, AC). A 42-day experimental period was conducted, with 14 days for adaptation and 28 days for treatment. Daily feed intake was recorded and various samples including feed, feces, rumen fluid, and blood were collected at different time points during the final week. The results indicated that the urea group had significantly higher dry matter intake, average daily gain, and gain efficiency in comparison to the AC group (P < 0.01). There was no difference in rumen pH and concentration of ammonia nitrogen between different groups (P > 0.05), but the rumen pH of urea group was higher than that of the AC group at 1 and 3 hours after feeding (P < 0.05). The urea group exhibited higher concentrations of total volatile fatty acids (VFA) and individual VFAs compared to the AC group at all-time points (P < 0.01). Compared to the urea group, the intake of all nutrients decreased in the AC group (P < 0.01), but the digestibility of dry matter and organic matter increased significantly (P < 0.01), and the digestibility of CP had an increasing trend (P = 0.06) in the AC group. Additionally, the urea group had lower levels of serum glucagon-like peptide-1, Peptide YY, Cl, total protein and globulin than the AC group (P < 0.05). The overall levels of HCO3 -, superoxide dismutase, glutathione peroxidase, catalase, albumin/globulin, blood urea nitrogen and total cholesterol in the urea group increased significantly compared to the AC group (P < 0.05). It was concluded that adding urea to the high-concentrate diet resulted in increased rumen pH and improved rumen fermentation and growth performance in fattening sheep compared to NH4Cl addition. Furthermore, urea addition improved sheep's antioxidant capacity and maintained their acid-base balance more effectively as compared to NH4Cl.